Company Performance Memoderasi Pengaruh Company Transparency, Corporate Social Responsibility, Karakteristik Eksekutif terhadap Tax Avoidance: pada Perusahaan Sektor Energy yang Terdaftar di BEI Periode Tahun 2018 - 2022 - Aah Koriah; Holiawati; Nofryanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to test Company Performance Moderating the Influence of Company Transparency, Corporate Social Responsibility, Executive Characteristics on Tax Avoidance. The purpose of this study is to see if company performance can moderate the impact of company transparency, corporate social responsibility, and executive characteristics on tax avoidance. This research is classified as quantitative. The data used is secondary information gathered from www.idx.co.id and the corporate website. This research's population consists of Energy Sector Companies Listed on the IDX from 2018 to 2022. Meanwhile, the sample for this study was established using a purposive sampling method, yielding 33 sample companies. The analytical method employed is Panel Data Model Regression analysis. The results of this research show that Company Transparency has no effect on Tax Avoidance, Corporate Social Responsibility has no effect on Tax Avoidance, Executive Characteristics has no effect on Tax Avoidance, Company Performance cannot moderate the effect of company transparency on tax avoidance, Company Performance cannot moderate the effect of Corporate Social Responsibility on tax avoidance, and Company Performance can moderate the influence of Executive Characteristics.